Sulfonamidoglycosylation of Methyl Glycosides Employing Perchloric Acid Supported on Silica Gel - Colinas, Pedro Alfonso (2008)
The sulfonamidoglycosylation of methyl glycosides in the presence of perchloric acid immobilized on silica gel proceeded effectively to afford the corresponding sulfonamido glycosides with good to high yields with minimal workup and short reaction times. This methodology was applied to the synthesis of some N-glycosyl sulfamides, which showed low nanomolar activity against human carbonic anhydrase.